What drives parental investments in early childhood? Experimental evidence from a video intervention in Rwanda - Patricia Justino; Marinella Leone; Pierfrancesco Rolla; Monique Abimpaye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper investigates the causal impact of a randomized video intervention designed to study the determinants of parental time investments in early childhood among low-income parents. We designed and screened a video that provided information and conveyed persuasive messages about the importance of parental investments in early childhood. In a second video, we added a positive feedback message to parents about their accomplishments during their participation in an earlier parenting program. We find that this second treatment (information plus feedback) improves maternal time investment by 0.2 SD. The provision of information without positive feedback was not enough to shift parental behavior on average but generated important heterogeneous effects. Notably, the poorest, most disadvantaged households benefited the most from both treatment arms. We explore the potential sources of these changes and document a weak impact of the treatments on parental self-efficacy and knowledge beliefs, but a strong positive effect of the treatments on social support within the community. This result suggests a potentially important role for social networks in parenting interventions in low-income settings.
Keywords: D83; D91; I25; J13; O55; 330; early childhood development; parental investments; beliefs; technology; human capital; Rwanda